Association of joint exposure to multiple brominated flame retardants with kidney impairment risk among adult population: Evidence from non-pooled samples of NHANES - Yi-Xiong Gao; Chen Kou; Xin Tan (Ecotoxicology and Environmental Safety)
Although previous studies showed toxicity of brominated flame retardants (BFRs) in human kidney cells in vitro, less is known about actual effects of BFRs exposure on kidney impairment. This study aims to examine associations of joint exposure to multiple BFRs with kidney impairment risk among adults, and with all-cause mortality risk among kidney impairment adults. Information on study participants and their serum concentrations of eleven BFRs (ten PBDEs and one PBB) were obtained from NHANES 2003–2004 and National Death Index. Factor analysis was applied to identify BFR exposure patterns. Data were analyzed using weighted multivariate logistic and Cox proportional regressions to examine the associations of BFR exposure patterns with kidney impairment risk and with all-cause mortality risk, respectively. Results showed concentrations of PBDE-28, PBDE-47, PBDE-85, PBDE-100, PBDE-154 and PBDE-66 among participants with kidney impairment were significantly higher than those without kidney impairment (all p < 0.050). Three exposure patterns were identified under an eigenvalue of ≥ 1.0 (p of Bartlett’s test: <0.001; KMO value: 0.787), and one pattern of them, which was characterized by high exposure to PBDE-28, PBDE-47, PBDE-85, PBDE-99, PBDE-154 and PBDE-66, was positively associated with kidney impairment risk (weighted covariates-adjusted OR: 1.317; 95 % CI: 1.031–1.683). The median of follow-up period was 190.0 months. All patterns were not significantly associated with all-cause mortality risk during the follow-up period (all p > 0.050). In conclusion, this study found for the first time that high exposure to some PBDEs may increase kidney impairment risk, but not directly affect prognosis of kidney impairment among adult population.